PERBANDINGAN HASIL EVALUASI PENGGUNAAN GOOGLE CLASSROOM DI MASA PANDEMI COVID-19 PADA TINGKAT SMP MENGGUNAKAN METODE HOT-FIT - Jihan Nur Syalsabila, Dodik Arwin Dermawan, Ahmad Heru Mujianto (JBT (JURNAL BISNIS dan TEKNOLOGI), 2022)
The impact of the Covid-19 pandemic for education is the change in the learning system from face-to-face to distance learning, many applications are able to support this distance learning, one of which is the google classroom. The features provided by Google Classroom itself can be said to be complete and this application is user friendly, so that users, bothstudents and teachers, are not difficult to access. in this research, we will discuss the comparison of the use of this application at the intermediate level, with two different places, this is useful for getting maximum results. To support this research, the method chosen is the HOT-Fit Model where this method is useful for evaluating a system. Distribution ofquestionnaires using purposive sampling technique, the number of respondents was 118 from two different schools. The results of this study, the comparative value of the evaluation of the use of google classroom was 71.57% for SMP IT Rohimana and 51.71% for MTSN 3 Jombang, from the two research sites stated that the google classroom application is good for use in distance learning.Keywords: Ration, Evaluation, google classtoom, Hot Fit, Covid-1